After school, then what?: government and private sector intervention in youth job training in Zimbabwe - Zvobgo, Rungano J. (Midlands State University, 2014)
This paper discusses efforts being made by the Government of Zimbabwe and the Private Sector to prepare youth/school leavers for the world of work. The paper asks the critical question School then what? enhancement of their employability? What training programmes exist? Who manages the programmes? How effective are they and what is their impact? It also compares the initiatives with the existing employment avenues and looks at their employment capacities. Overall, the paper shows the contribution of government technical and vocational training colleges, as well as agricultural colleges, and that of registered and unregistered private vocational training institutions to the training of youths for jobs in Zimbabwe.